Perlindungan Hukum Terhadap Orang Dengan Gangguan Jiwa Sebagai Korban Penganiayaan - Hasanudin, Dahlia; Toule, Elsa Rina Maya; Saimima, Judy Marria (PATTIMURA Law Study Review, 2024)
ABSTRACT: Indonesia is a rule of law country where there is always recognition and protection of human rights. Legal protection by the state is one of the absolute elements that can create peace, peace and order regarding human rights as contained in the 1945 Constitution of the Republic of Indonesia. The government has an obligation to fulfill the rights of every citizen without any discrimination in various aspects. However, in reality, in everyday life there are still frequent violations related to human rights experienced by people with mental disorders (ODGJ). People with mental disorders often receive negative stigma from society. The stigma obtained is in the form of discrimination and even violence. One of the acts of violence experienced by ODGJ is acts of abuse. The research method used in this research is the Normative Law research method. The problem approaches used are the statutory approach, conceptual approach and case approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The procedure for collecting legal materials uses library research, as well as analyzing legal materials using qualitative analysis methods by interpreting the legal materials that have been processed. Based on the research results, it can be concluded that legal protection for ODGJ has been regulated in various laws and regulations, including: the 1945 Constitution of the Republic of Indonesia, Law no. 36 of 2009 concerning Health, Law no. 18 of 2014 concerning Mental Health, Law no. 8 of 2016 concerning Persons with Disabilities. and the Criminal Code, which was created to guarantee that ODGJ receive health protection and protection from various acts of violence. Criminal liability for perpetrators of abuse of ODGJ can be sentenced to criminal penalties if they are proven to fulfill the elements of a criminal act of abuse, namely: an unlawful act. The act causes suffering or injury, the act is done intentionally. In case Number: 44/Pid.B/2022/PN Msh. The panel of judges sentenced the defendant Mahmud Refra to prison for 4 (four) years and 6 (six) months. Because he has been legally and convincingly proven guilty of committing the crime of torture which resulted in death in accordance with the subsidiary indictment and acquitted the defendant from the primary indictment of the public prosecutor. By paying attention to the facts revealed at trial.